Advantages and Disadvantages of Educational Email Alerts for Family Physicians: Viewpoint - Badran, Hani; Pluye, Pierre; Grad, Roland (JMIR Publications, 2015)
BackgroundElectronic knowledge resources constitute an important channel for accredited Continuing Medical Education (CME) activities. However, email usage for educational purposes is controversial. On the one hand, family physicians become aware of new information, confirm what they already know, and obtain reassurance by reading educational email alerts. Email alerts can also encourage physicians to search Web-based resources. On the other hand, technical difficulties and privacy issues are common obstacles. ObjectiveThe purpose of this discussion paper, informed by a literature review and a small qualitative study, was to understand family physicians' knowledge, attitudes, and behavior in regard to email in general and educational emails in particular, and to explore the advantages and disadvantages of educational email alerts. In addition, we documented participants' suggestions to improve email alert services for CME. MethodsWe conducted a qualitative descriptive study using the "Knowledge, Attitude, Behavior" model. We conducted semi-structured face-to-face interviews with 15 family physicians. We analyzed the collected data using inductive-deductive thematic qualitative data analysis. ResultsAll 15 participants scanned and prioritized their email, and 13 of them checked their email daily. Participants mentioned (1) advantages of educational email alerts such as saving time, convenience and valid information, and (2) disadvantages such as an overwhelming number of emails and irrelevance. They offered suggestions to improve educational email. ConclusionsThe advantages of email alerts seem to compensate for their disadvantages. Suggestions proposed by family physicians can help to improve educational email alerts.